The rapid expansion of Indonesia’s platform economy - Jose Segitya Hutabarat; Valeri Timoti Hamise (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2026)
This study develops the Climate-Informed Flexibility Vulnerability Index (CAFVI) to measure multidimensional climate–labor vulnerability among platform workers in Jakarta, Indonesia. The index integrates four dimensions: economic vulnerability, institutional vulnerability, demographic sensitivity, and environmental exposure. Using secondary data from Fairwork Indonesia, BPS Sakernas, and BMKG, the study applies variable normalization, equal weighting, and principal component analysis to produce comparable vulnerability scores across age groups and platform providers. The findings show a clear U-shaped pattern of vulnerability, with the highest scores observed among younger and older workers and the lowest among prime-age workers. At the platform level, vulnerability is shaped primarily by the interaction between institutional protection and income conditions, while environmental exposure functions as a shared structural baseline. Principal component analysis confirms the internal coherence of the index, with the first component explaining most of the total variance and all loadings remaining positive. The results indicate that climate stress does not operate independently but intensifies existing labor precarity where worker protection and income stability are weak. This study contributes by extending platform labor analysis beyond conventional fairness assessments and by offering a transparent, replicable framework for evaluating climate-sensitive labor vulnerability in data-constrained urban settings, especially in the Global South and comparable emerging economies.